A pseudoautosomal glycosylation disorder prompts the revision of dolichol biosynthesis - Wilson, Matthew P; Kentache, Takfarinas; Althoff, Charlotte R; Schulz, Céline; de Bettignies, Geoffroy; Mateu Cabrera, Gisèle; Cimbalistiene, Loreta; Burnyte, Birute; Yoon, Grace; Costain, Gregory; Vuillaumier-Barrot, Sandrine; Cheillan, David; et al. (Cell, 2024)
Dolichol is a lipid critical for N-glycosylation as a carrier for activated sugars and nascent oligosaccharides. It is commonly thought to be directly produced from polyprenol by the enzyme SRD5A3. Instead, we found that dolichol synthesis requires a three-step detour involving additional metabolites, where SRD5A3 catalyzes only the second reaction. The first and third steps are performed by DHRSX, whose gene resides on the pseudoautosomal regions of the X and Y chromosomes. Accordingly, we report a pseudoautosomal-recessive disease presenting as a congenital disorder of glycosylation in patients with missense variants in DHRSX (DHRSX-CDG). Of note, DHRSX has a unique dual substrate and cofactor specificity, allowing it to act as a NAD+-dependent dehydrogenase and as a NADPH-dependent reductase in two non-consecutive steps. Thus, our work reveals unexpected complexity in the terminal steps of dolichol biosynthesis. Furthermore, we provide insights into the mechanism by which dolichol metabolism defects contribute to disease.
Keywords: vrozené poruchy glykosylace; Membrane Proteins; dolichal; Humans; Mutation, Missense; Female; polyprenol; dolichol; congenital disorders of glycosylation; lidé; pseudoautosomal region; polyprenal; Congenital Disorders of Glycosylation; polyisoprenoids; missense mutace; glykosylace; ženské pohlaví; Male; lipid droplets; 3-Oxo-5-alpha-Steroid 4-Dehydrogenase; 3-oxo-5-alfa-steroid-4-dehydrogenasa; membránové proteiny; mužské pohlaví; N-glycosylation; Glycosylation; Dolichols